A case study of the efficiency on allocation of fund in Pejabat Agama Islam Daerah Hulu Selangor / Nurul Husna Zainal Abidin - Zainal Abidin, Nurul Husna (2009)
Fund is the process of funding, or providing capital (funds) for a transaction, a project, a person, a business or other private or public institutions. Budget is also important to manage the fund. A budget is a money plan. With it, you can organize and control your financial resources, set and realize goals, and decide in advance how your money will work for you. A budget can be as simple as it is powerful. The budget planning is the forecasting made by the corporation, and it becomes one of the measures to check whether the organizational goals are achieved. The reasons for over or under-estimation can also be expressed in figures as for example objectively presented. The budget planning could contain cost accounting, sales forecasting, trading and profit and loss forecasting, balance sheet forecasting, and cash and fund flow forecasting. These all statements are made out before the accounting period, and could be adjusted during the periods in case of needs. The reviews could be done monthly, quarterly or/and yearly. The actual figures will be compared with the budgeted figures. Therefore, the reasons of unmatched part of whole budget can easily been seen and analyzed. This case study will discuss about the efficiency on allocation of fund in Pejabat Agama Islam Daerah Hulu Selangor. The purpose of this study is to determine whether this organization manages the funds well or the method that they use is still relevant to use for the future. Or they have to change and to looking for other solution.